Ensuring the required level of reliability during the design stage of -latticed shells with a large opening - Gorokhov, Yevgen; Mushchanov, Volodymyr; Pryadko, Iurii (Journal of Civil Engineering and Management, 2015)
The article describes the design technique, which is based on determination of numerical parameters pertaining to reliability of long-span latticed roofs with a large opening formed using the system made of rigid threads. The suggested algorithm is based on experimental and fundamental research focused on the stress/strain state of a spatial roof model and the operation of design combination of loads. It suggests a solution to a series of problems: determining rational geometric parameters for a structure; obtaining corresponding rigid characteristics of the principal load-bearing members; determining the trajectory of member failure for a typical shell structure with a resulting estimation of stress/strain state of a structure; determining numerical parameters of reliability of a designed structure (determining the lower and upper limits of reliability). The proposed algorithm is limited by static loads and state requirements on strength limits. The example of a design for a spatial latticed shell formed using the system of flexurally stiff threads has been given according to the above-described algorithm.